2016
DOI: 10.1111/phis.12081
|View full text |Cite
|
Sign up to set email alerts
|

Practical Perception and Intelligent Action

Abstract: Perceiving things to be a certain way may in some cases lead directly to action that is intelligent (e.g., skillful, wise, clever, astute). This phenomenon has not often been discussed, though it is of broad philosophical interest. It also raises a difficult question: how can perception produce intelligent action? After clarifying the question-which I call the question of "practical perception"-and explaining what is required for an adequate answer, I critically examine two candidate answers drawn from work on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 74 publications
0
2
0
Order By: Relevance
“…This act could be suggested to incur an organic behavioural change, merely through increased awareness of different or possibly more favourable leadership behaviours. A new knowledge base may alter the individual's understanding of identity leadership and perception of their own leadership, leading to new and recognisable 'intelligent action' (Bengson, 2016). For example, in the current study we found the largest differences between experimental and control group in impresarioship.…”
Section: Discussionmentioning
confidence: 44%
“…This act could be suggested to incur an organic behavioural change, merely through increased awareness of different or possibly more favourable leadership behaviours. A new knowledge base may alter the individual's understanding of identity leadership and perception of their own leadership, leading to new and recognisable 'intelligent action' (Bengson, 2016). For example, in the current study we found the largest differences between experimental and control group in impresarioship.…”
Section: Discussionmentioning
confidence: 44%
“…11 Cf. e.g.,(Peacocke, 1992, 29-33),(Bealer, 1998),(Bengson, 2016),(Balcerak Jackson & Balcerak Jackson, 2012); a similar argument is made in(Rattan & Wikforss, 2017). 12 Cf.…”
mentioning
confidence: 71%